Water and Meadow Views Both Afford Perceived but Not Performance-Based Attention Restoration: Results From Two Experimental Studies - Johnson, Katherine A.; Pontvianne, Annabelle; Ly, Vi; Jin, Rui; Januar, Jonathan Haris; Machida, Keitaro; Sargent, Leisa D.; Lee, Kate E.; Williams, Nicholas S. G.; Williams, Kathryn J. H. (Frontiers in Psychology, 2022)
Attention Restoration Theory proposes that exposure to natural environments helps to restore attention. For sustained attention—the ongoing application of focus to a task, the effect appears to be modest, and the underlying mechanisms of attention restoration remain unclear. Exposure to nature may improve attention performance through many means: modulation of alertness and one’s connection to nature were investigated here, in two separate studies. In both studies, participants performed the Sustained Attention to Response Task (SART) before and immediately after viewing a meadow, ocean, or urban image for 40 s, and then completed the Perceived Restorativeness Scale. In Study 1 (n = 68), an eye-tracker recorded the participants’ tonic pupil diameter during the SARTs, providing a measure of alertness. In Study 2 (n = 186), the effects of connectedness to nature on SART performance and perceived restoration were studied. In both studies, the image viewed was not associated with participants’ sustained attention performance; both nature images were perceived as equally restorative, and more restorative than the urban image. The image viewed was not associated with changes in alertness. Connectedness to nature was not associated with sustained attention performance, but it did moderate the relation between viewing the natural images and perceived restorativeness; participants reporting a higher connection to nature also reported feeling more restored after viewing the nature, but not the urban, images. Dissociation was found between the physiological and behavioral measures and the perceived restorativeness of the images. The results suggest that restoration associated with nature exposure is not associated with modulation of alertness but is associated with connectedness with nature.